Oxygen Sensing: Physiology and Pathophysiology - Philip I. Aaronson; Asuncion Rocher (MDPI AG, 2022)
Oxygen is such an essential element for life that multiple mechanisms have evolved to maintain oxygen homeostasis, including those which detect decreases in arterial O2 and generate adaptive responses to hypoxia [...]